Novel preparation of transdermal drug-delivery patches and functional wound healing materials. - Ahmad, Z; Stride, E; Edirisinghe, M (2009)
The application of an electric field to a flowing medium can result in the formation of microscale and nanoscale structures suitable for drug delivery applications. We show that the design of the drug carrier can be varied and the release mechanism can be controlled by changing the physical state of the component containing the active agent. The structures formed include loaded micrometer-scale tubes and microcapsules and nanocapsules, which can also be utilized together to fabricate patches and wound healing materials. The aim of this study was to demonstrate novel processing of such patches and wound dressings. The processing used to generate these structures is carried out at the ambient temperature and is a versatile one-step operation suitable for a range of materials with low running costs and set-up costs without the degradation of the active drug component. The process can be multiplexed and requires no solvent extraction. It also offers pharmaceutical applications outside the remit of the potential uses presented.